Efficacy of methyl jasmonate-liposomes on 'Kluai Khai' bananas (Musa AA) quality preservation and oxidative response alleviation during room temperature storage - Da, Li; Youryon, Pannipa; Suo, Xiaoyu; Sinthusamran, Sirima; Phakawan, Janejira; Techavuthiporn, Chairat; Supapvanich, Suriyan (My University, 2025)
The rapid acceleration of ripening during ambient storage is a primary factor limiting the shelf-life of bananas. Application of methyl jasmonate (MeJA) has been used to enhance the postharvest quality of perishable commodities. This study aimed to investigate the efficacy of MeJA (10−3 M) encapsulated in liposomes (MeJA-liposomes) on the postharvest quality of ‘Kluai Khai’ bananas (Musa AA) during storage at room temperature (26 ± 2 °C) for 9 d The MeJA-liposomes exhibited an average particle size of 152.37 ± 1.63 nm with a PDI of 0.21 and a zeta potential value of -33.9 ± 1.02 mV. The MeJA-liposomes treatment exhibited a greater delay in fruit ripening and peel colour development compared to the MeJA (10−3 M), blank-liposomes, and control treatments, respectively. MeJA-liposomes reduced the oxidative stress of the peel by decreasing electrolyte leakage, lipoxygenase activity, and the levels of malondialdehyde, α-fanesene, conjugated triene (CT-281) and H2O2 in the fruit peel. As the ripening process in untreated bananas progressed, they exhibited greater antioxidant activities, namely in terms of ferric reduction antioxidant capacity and DPPH radical scavenging activity in the peel, compared to the MeJA-liposome-treated bananas. The application of MeJA-liposomes treatment resulted in a postponement in the process of softening and an increase in the levels of total soluble solids content, and BrimA in the banana pulp throughout the storage period. In conclusion, the application of MeJA-liposomes presents a promising method for postponing the ripening process, alleviating the oxidative response in the peel and prolonging the shelf-life of ‘Kluai Khai’ bananas (Musa AA) at room temperature.
Keywords: Liposomes; Membrane peroxidation; Methyl jasmonate; Musa AA; Ripening